Empowering Students Through Elective Grading in a University Setting - Telles-Langdon, David; Telles-Langdon, Neill (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
In undergraduate university courses, the assessment methods often lack variety, which can lead to significant stress for both students and educators. It is becoming increasingly apparent that incorporating a range of assessment types could alleviate this stress and better accommodate diverse learning styles (Leite et al., 2010). Elective Grading (EG) is an approach to assessment that empowers students to determine their own grade weighting, based on their own learning goals and progress. EG can be implemented by using simple algebraic formulas to increase or decrease the original grade by the amount elected by the student. Using computer-based spreadsheet technology, EG can be included in a dynamic system that responds to the student's work, rather than relying solely on the instructor's evaluation. This article explains the rationale behind adopting an EG system, exploring a different option for students to re-weigh tests and assignments to reduce the perceived impact of each assessment, with no grade inflation. This flexible approach can mitigate student stress and anxiety, and practical strategies for its implementation across the curriculum. EG can enhance student learning and engagement from both the instructor's and the students’ perspectives. Students can use EG to adapt their own assessment preferences that may reduce stress and improve learning outcomes.